Seasonal Occurrence and Carbapenem Susceptibility of Bovine Acinetobacter baumannii in Germany - Klotz, Peter; Higgins, Paul G.; Schaubmar, Andreas R.; Failing, Klaus; Leidner, Ursula; Seifert, Harald; Scheufen, Sandra; Semmler, Torsten; Ewers, Christa (Frontiers in Microbiology, 2019)
Acinetobacter baumannii is one of the leading causes of nosocomial infections in humans. To investigate its prevalence, distribution of sequence types (STs), and antimicrobial resistance in cattle, we sampled 422 cattle, including 280 dairy cows, 59 beef cattle, and 83 calves over a 14-month period. Metadata, such as the previous use of antimicrobial agents and feeding, were collected to identify putative determining factors. Bacterial isolates were identified via MALDI-TOF/MS and PCR, antimicrobial susceptibility was evaluated via VITEK2 and antibiotic gradient tests, resistance genes were identified by PCR. Overall, 15.6% of the cattle harbored A. baumannii, predominantly in the nose (60.3% of the A. baumannii isolates). It was more frequent in dairy cows (21.1%) than in beef cattle (6.8%) and calves (2.4%). A seasonal occurrence was shown with a peak between May and August. The rate of occurrence of A. baumannii was correlated with a history of use of 3rd generation cephalosporins in the last 6 months prior to sampling Multilocus sequence typing (Pasteur scheme) revealed 83 STs among 126 unique isolates. Nine of the bovine STs have previously been implicated in human infections. Besides known intrinsic resistance of the species, the isolates did not show additional resistance to the antimicrobial substances tested, including carbapenems. Our data suggest that cattle are not a reservoir for nosocomial A. baumannii but carry a highly diverse population of this species. Nevertheless, some STs seem to be able to colonize both cattle and humans.